In Pursuit of Ecological Forestry: Historical Barriers and Ecosystem Implications - Gresh, James M.; Courter, Jason R. (Frontiers in Forests and Global Change, 2021)
The global need for ecological forestry is more important today than ever. But despite a century of technical advancements from forestry leaders—especially in North America and Europe—the world's forest ecosystem is declining at a time when carbon levels are rising, and biodiversity is at risk. Unfortunately, even the world's innovation leaders are struggling to change industry practices in their home countries. Undeterred by the lack of progress, new efforts are being attempted with Europe taking a markedly different path than the U.S. In the U.S., the pursuit of ecological forestry has embraced natural disturbance frameworks and stresses customized goals for local environments and social demands. In Europe, a broad application of low-intensity harvest protocols and canopy protection is being promoted for many forest types. The U.S. approach shows strong ecological promise at local and regional scales, but its broad adoption within the industry as a whole is limited and inconsistent. For the European approach, the broadly elevated priority of continuous canopy draws scientific critics, but their forestry industry is adopting and applying the concept. Although lower-intensity harvests are common to both regions, evidence suggests that Europe may be using low-intensity methods too broadly, while the U.S. is using them too little. The objective of this perspective is to describe the historical development of ecological forestry in Europe and the United States, and to propose research adjustments to help America pursue broader ecological forestry application. By understanding the historical precedents that influence forestry perceptions and the differences in contemporary approaches among forestry leaders, forestry scientists may be better equipped to design research and promote practices that can influence industry behavior for better ecosystem implications.